Oocyte Retrieval in Asymptomatic Patients Positive for SARS-CoV-2. (12th August 2022) - Akers, Allison; New, Erika P.; Plosker, Shayne; Silva, Celso P.; Sprague, Rachel; Imudia, Anthony N.
Abstract : Objective . To report two cases of oocyte retrieval performed in asymptomatic SARS-CoV-2-positive patients. Design . Case report. Setting . Outpatient private practice infertility center. Patients . A 28-year-old woman at risk for OHSS who took her trigger injection prior to testing positive for SARS-CoV-2 and a 19-year-old oncofertility patient who tested positive prior to retrieval due to a family exposure. Both patients were asymptomatic. Main Outcome Measures . Cycle outcomes, patient safety, and staff safety. Results . Both patients underwent successful oocyte retrieval procedures without developing symptoms or complications from COVID-19. No staff members that cared for these patients developed symptoms of COVID-19. Conclusion . Worsening fertility outcomes and potential for psychological and financial burdens to the patient must be balanced with risk of perioperative complications in patients testing positive for SARS-CoV-2. As we continue to provide fertility care in a world with COVID-19, appropriate risk mitigation strategies should be implemented to minimize exposure to SARS-CoV-2.